The reconstruction of social ties for refugee women: research hints from Italy and Bulgaria - Ruspini, Paolo; Hristov, Petko (Comparative Cultural Studies: European and Latin American Perspectives, 2024)
Previous research shows the importance of building up self-help structures in a transnational perspective for the inclusion of migrant women who are fleeing their home countries because of war, violence, or different forms of vulnerability. The mobilization of self- help organizations through the intersection of transnationalism and gender is a useful practice-oriented pedagogy directed both towards the most vulnerable groups of women, or those already empowered either as community leaders or network facilitators, other migrants and the whole native population. The article compares the traumatic refugee experience of two women with different fates, fleeing the hostilities in their native countries – the Democratic Republic of the Congo and Ukraine. The two video interviews were made in Bulgaria and Italy, which are important host countries on the south-eastern or southern external border of the European Union. The research questions focus on three main themes: 1) Self-organization and mutual aid among women asylum seekers; 2) Building own social networks through transnational practices and adaptation in host communities; 3) Gender and ethnic basis of community or individual empowerment of refugee women. The final aim of this investigation is to analyse patterns of social networks’ creation among refugee women originating from different socio-cultural contexts. The research findings might be useful to instill inclusion practices which are apt to refugee women empowerment.